Efektivitas Pengelolaan Tambang Pasir Wae Lengkas terhadap Perekonomian Masyarakat di Kelurahan Golo Dukal Kabupaten Manggarai (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Indonesia possesses abundant natural resources, including mineral resources that play a strategic role in improving community welfare. One form of community-based mining that continues to develop is traditional sand mining, such as the Wae Lengkas Sand Mine located in Golo Dukal Village, Manggarai Regency. This study aims to analyze the effectiveness of sand mining management and its contribution to the local community’s economic conditions. The research employs a qualitative method with a phenomenological approach and a case study design. Data were collected through in-depth interviews, field observations, and documentation, with informants selected using purposive and snowball sampling techniques. Data analysis was conducted using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the management of the Wae Lengkas sand mine has not been fully effective. The organizing and actuating aspects function relatively well due to strong kinship values and active community participation. However, the planning and controlling aspects remain weak, particularly regarding legal licensing, technical planning, occupational safety, and environmental impact control. The main inhibiting factors include limited technology, minimal government support, low human resource capacity, and inadequate supporting facilities. Therefore, stronger government involvement through assistance, regulatory socialization, training programs, and supervision is required to ensure that community-based sand mining management becomes more effective, safe, and sustainable while providing long-term economic benefits for local communities.